Equimolar bimetallic vanadium titanium based Prussian blue analogue as zero strain cathode for sodium ion batteries - Javed, Omama; Mehek, Rimsha; Ali, Ghulam; Radhiyah, Abd Aziz (Elsevier, 2025)
Prussian blue analogues (PBAs) are attractive cathode materials for sodium-ion batteries because of their open framework, rapid ion transport, and low-cost aqueous synthesis; however, electrochemical performance is often limited by defect/water chemistry and the associated structural instability during cycling. Here, we report an equimolar bimetallic titanium/vanadium PBA, Na₂Ti₀.₅V₀.₅[Fe(CN)₆], synthesized by a simple solution precipitation route and systematically compared with non-equimolar Ti/V analogues prepared under identical conditions. X-ray diffraction confirms a single-phase cubic framework (Fm3‾m). In non-aqueous Na half-cells (2.0–4.5 V vs. Na/Na+), Na₂Ti₀.₅V₀.₅[Fe(CN)₆] delivers an initial discharge capacity of 68.7 mAh g− 1 at 0.1C and retains 62.35 mAh g− 1 after 200 cycles (≈90.8 % retention) with near-unity Coulombic efficiency. Rate capability (0.1C → 10C → 1C) shows stable capacity at high rates and clear recovery on returning to lower current. Electroanalytical measurements indicate favorable kinetics: EIS reveals reduced charge-transfer resistance for the equimolar composition, and CV scan-rate analysis yields an apparent Na+ diffusion coefficient of 2.33 × 10− 8 cm2 s − 1 . In situ XRD demonstrates single-phase Na+ (de)insertion with highly reversible lattice breathing; quantitative lattice-parameter tracking gives a maximum volumetric strain of ~0.07 %, supporting a near-zero-strain mechanism. TGA confirms reduced water content for the equimolar material, consistent with its enhanced phase stability.